2017
DOI: 10.1016/j.neulet.2017.08.072
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar pathology in childhood-onset vs. adult-onset essential tremor

Abstract: Although the incidence of ET increases with advancing age, the disease may begin at any age, including childhood. The question arises as to whether childhood-onset ET cases manifest the same sets of pathological changes in the cerebellum as those whose onset is during adult life. We quantified a broad range of postmortem features (Purkinje cell [PC] counts, PC axonal torpedoes, a host of associated axonal changes [PC axonal recurrent collateral count, PC thickened axonal profile count, PC axonal branching coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Therefore, we chose the age of onset of 50 to divide the early vs. late onset ET cases. Using data from our previous publications on the PC pathology in subgroups of ET cases and controls [21,24,25], we determined that with each ET group and control group composed of 30 subjects, we would be powered at 90% to detect differences of the magnitude previously detected [21,24,25]. Accordingly, we randomly selected 30 early onset ET cases, 30 late onset ET cases, and 30 controls in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we chose the age of onset of 50 to divide the early vs. late onset ET cases. Using data from our previous publications on the PC pathology in subgroups of ET cases and controls [21,24,25], we determined that with each ET group and control group composed of 30 subjects, we would be powered at 90% to detect differences of the magnitude previously detected [21,24,25]. Accordingly, we randomly selected 30 early onset ET cases, 30 late onset ET cases, and 30 controls in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, we randomly selected 30 early onset ET cases, 30 late onset ET cases, and 30 controls in the current study. Of the selected cases for this study, data from 14 of 30 controls and 15 of 60 ET cases were reported in prior publications [21,24,25]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] A significant role of the cerebellum in the pathophysiology of both essential tremor and dystonia has recently been postulated and related to a decreased Purkinje cell density. 19,20 Such pathophysiologic similarities of dystonic and essential tremor could be linked to tremor improvement with alcohol intake in both diseases. Our results thus suggest that alcohol responsiveness may not be a reliable marker to support a diagnosis of essential tremor over a diagnosis of dystonic tremor.…”
Section: Figure Degree Of Alcohol Responsiveness Across Different Dysmentioning
confidence: 99%
“…ET is not a disease exclusively of adults; indeed, the disease may begin in childhood [62][63][64]. The majority of these young-onset cases are familial [65,66].…”
Section: Agementioning
confidence: 99%